Utilizing Snort in the Analysis of Intrusion Detection System - Noorulsadiqin Azbiya, Yaacob (2003)
The objective of this research is primarily to construct a set of intrusion detection system evaluation. The set is built through four basic needs of instrusion detection as stated by Porras and Valdes (1998) and Debar et. al (1999) which comprise of accuracy, performance, completeness and fault tolerance. The test set builts is then tested by using open instrusion detection system, Snort. The methodology and the testing procedure which are used during the evaluation of intrusion detection system is based on a simulation model. Results from the evaluation set constructed is found able to expose any existing weakness in the intrusion detection system. Any weaknesses detected will then be used to upgrade the intrusion detection system from time to time.